Evaluation of plaque index, gingival index and oral health-related quality of life in obese patients = Evaluación del índice de placa, índice gingival y calidad de vida relacionada con la salud bucal en pacientes obesos - Ayan, Gizem; Dayı, Burak (2023)
Obesity is a chronic disease that may be related to caries, periodontitis, xerostomia, and dental erosion, as well as increasing morbidity and mortality. The aim of this study was to evaluate the plaque index (Silness & Löe, 1964), the gingival index (Löe & Silness, 1963), and the oral health-related quality of life (OHRQoL) in obese patients. The study included 45 extremely obese, 45 obese, and 45 normal-weight individuals between the ages of 18 and 58. The plaque index and gingival index of the individuals were determined by clinical examination by probing. In addition, the Oral Health Impact Profile-14 (OHIP-14) questionnaire was used for the OHRQoL. The IBM SPSS Statistic 22.0 software program was used for the statistical evaluation of the study data. The plaque index and gingival index values were statistically higher in obese compared to normal weight individuals (p<0.05). Both plaque index and gingival index values were not statistically significant between the extremely obese and control groups (p>0.05). There was no statistically significant difference between the OHIP-14 total scores of the groups (p>0.05). Increased apparent plaque index and gingival index values in obese patients may adversely affect periodontal health.
La obesidad es una enfermedad crónica que puede estar relacionada con caries, periodontitis, xerostomía y erosión dental, además de aumentar la morbimortalidad. El objetivo de este estudio fue evaluar el índice de placa, el índice gingival y la calidad de vida relacionada con la salud bucal (CVSB) en pacientes obesos. El estudio incluyó a 45 individuos extremadamente obesos, 45 obesos y 45 de peso normal entre las edades de 18 y 58 años. El índice de placa y el índice gingival de los individuos se determinaron mediante examen clínico y sondaje periodontal. Además, se utilizó el cuestionario Oral Health Impact Profile-14 (OHIP-14) para la evaluación CVSB. Se utilizó el programa informático IBM SPSS Statistic 22.0 para la evaluación estadística. Los valores del índice de placa y del índice gingival fueron estadísticamente más altos en obesos en comparación con los individuos de peso normal (p<0,05). Tanto el índice de placa como el índice gingival no fueron estadísticamente significativos entre los grupos de control y extremadamente obesos (p>0,05). No hubo diferencia estadísticamente significativa entre las puntuaciones totales de OHIP-14 de los grupos (p>0,05). El aumento del índice de placa aparente y los valores del índice gingival en pacientes obesos pueden afectar negativamente la salud periodontal.
En revista Odóvtos, vol. 25, no.1 (enero-abril 2023)
Descripción basada en el contenido visto el 13 de diciembre, 2024
También disponible en formato HTML y EPUB